FENOMENA PENGGUNA APLIKASI LIVE STREAMING MANGO LIVE DI KALANGAN MAHASISWA - Setyanugraha, R. Satria; Nur Amalia, Zahwa; Asriandhini, Bunga (Awatara Publisher, 2024)
Social media has become an inseparable part of communication activities in the digital era. In everyday life, social media has become a tool for human communication and has become a new lifestyle. Not only for obtaining information, social media has now become a platform for interacting, expressing yourself and even sharing it to show to the public. Live streaming is a social media application that broadcasts individual activities online. Mango Live is a live streaming application originating from India, this application can be downloaded on Google Play or the Apple Store. According to data on Google Play and Apple Store, Mango Live is a streaming service intended for users with an age limit of 17 years and over, is the best global live broadcast platform that focuses on entertainment, lifestyle and broadcasting from talented hosts. The aim of this research is to find the motives and interactions used in the phenomenon of using the Mango Live live streaming application among students. This research uses qualitative methods with Alfred Schutz's phenomenological theory. Alfred Schutz's phenomenological theory looks for the causes and goals of students in using the Mango Live application. From the results of this research, there are entertainment motives to fill free time, economic motives to earn income, motives to seek experience for the achievement process, and motives to express oneself to build self-confidence. Researchers revealed that the interactions used in using the Mango Live application are in the comments feature, follow feature, communication feature and virtual gift feature.